2018
DOI: 10.11621/pir.2018.0111
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of semantic aphasia in spanish speaking patient

Abstract: Background. Aphasia is defined as a language disorder resulting from brain damage. The establishment of the relationship between the assessment and the procedures for rehabilitation is one of fundamental aspects of clinical neuropsychology.Objective. The objective of this study is to describe the case of a Spanish-speaking patient with semantic aphasia, along with the strategies used in her neuropsychological assessment, and the procedures and results of her rehabilitation.Design. The study method consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…According to the data of difficulties of adults with posterior brain damage, detected specifically in drawing tasks and similar difficulties in little children who aren't able to follow tasks of graphic activity, it's logic to suppose that guided introduction and formation of graphic activity by levels might help both processes of development in children and rehabilitation in adults and adolescents (Solovieva & Quintanar, 2017b, 2018a, 2018b. Our results show positive effect of development of drawing activity in children (Solovieva & Quintanar, 2017b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the data of difficulties of adults with posterior brain damage, detected specifically in drawing tasks and similar difficulties in little children who aren't able to follow tasks of graphic activity, it's logic to suppose that guided introduction and formation of graphic activity by levels might help both processes of development in children and rehabilitation in adults and adolescents (Solovieva & Quintanar, 2017b, 2018a, 2018b. Our results show positive effect of development of drawing activity in children (Solovieva & Quintanar, 2017b).…”
Section: Resultsmentioning
confidence: 99%
“…One of our studies showed how drawing tasks helped for rehabilitation of spatial analysis and synthesis in adult patient with semantic aphasia (Solovieva & Quintanar, 2018b). The patient was systematically trained to use own reflection for analysis of relation between details in objects and representations.…”
Section: Resultsmentioning
confidence: 99%